Management of Complex Third-Degree Burn with Multi-Drug-Resistant Infection Using Instillation Negative Pressure Wound Therapy and PHMB irrigation solution: A Case Report - Tianwattanatada, Suttipong; Muangman, Pontakorn; Sornmanapong, Tanut; Roeksomtawin, Sompol; Chinaroonchai, Kusuma (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Severe burn injuries complicated by multi-drug-resistant infections and systemic organ dysfunction pose significant treatment challenges. Advanced wound care techniques like negative pressure wound therapy with instillation (NPWTi) have shown promise in enhancing wound healing and controlling local infections. Polyhexanide-based irrigation solution offers antimicrobial effects and biofilm disruption, improving wound bed preparation. We report a case of a 65-year-old male with a third-degree burn involving 15% of the total body surface area on his right leg, caused by prolonged contact with hot coals during sleep. Despite multiple debridements at the initial hospital, the wound deteriorated, exhibiting thick slough, purulent discharge, and tibial bone exposure. Upon referral, the patient showed signs of sepsis, acute kidney injury, and acute lung injury. Broad-spectrum intravenous antibiotics were initiated. Tissue cultures identified Carbapenem-Resistant Enterobacteriaceae (Klebsiella pneumoniae) and multi-drug-resistant Pseudomonas aeruginosa. Local management included surgical and chemical debridement followed by NPWTi with Polyhexamethylene biguanide hydrochloride irrigation. This treatment promoted rapid granulation tissue formation and significantly reduced bacterial load, confirmed by follow-up cultures. However, systemic complications arose, including secondary fungal infection and worsening renal function. After multidisciplinary evaluation, an above-knee amputation was performed as a life-saving intervention. This case underscores the critical importance of early and aggressive infection control using NPWTi with polyhexanide in managing complex burn wounds, while systemic factors remain key determinants of patient outcomes.